The Ownership of Land in the Majibacoa Region during the Colonial Period up to 1867 (Islas, 2025)
Introduction: The municipality of Majibacoa was founded in 1976. The aim of this article is to offer an approach to the history of colonial land ownership within the current boundaries of Majibacoa, from its origins until 1867, in support of the stated assertion.Methods: This study is grounded in regional and local history, employing methods of logical reasoning, analogical-comparative analysis, and hermeneutics for the interpretation of collected documents.Results: It was confirmed that the former communal estates located in what is now the municipality of Majibacoa reveal the historical roots of its cultural identity.Conclusions: The colonial communal estates in Majibacoa contributed to the formation of a growing Criolla identity, rooted in family lineages and a strong sense of belonging to the native region.
Keywords: land ownership; communal estates; Majibacoa; cultural identity